Systematic Review and Meta-Analysis to Establish the Association of Common Genetic Variations in Vitamin D Binding Protein With Chronic Obstructive Pulmonary Disease - Khanna, Ritesh; Nandy, Debparna; Senapati, Sabyasachi (Frontiers in Genetics, 2019)
ABSTRACT Background: Vitamin-D binding protein (DBP) also known as GC protein, is a major determinant for vitamin- D metabolism and transport. GC1F, GC1S and GC2 are the three allelic variants (denoted as rs4588 and rs7041) of GC, and known to be associated with chronic obstructive pulmonary disease (COPD). However, contradictory reports and population specific risk attributed by these alleles warranted detailed genetic epidemiology study to establish the association between GC variants and COPD. In this study we performed a meta-analysis and investigated the genetic architecture of GC locus to establish the association and uncover the plausible reason for allelic heterogeneity. Methods: Published cross-sectional case control studies were screened and meta-analysis was performed between GC variants and COPD outcome. RevMan-v5.3 software was used to perform random and/or fixed models to calculate pooled odds ratio (Meta-OR). Linkage disequilibrium (LD) and haplotypes at GC locus were evaluated using 1000 genomes genotype data. In silico functional implications of rs4588 and rs7041 was tested using publicly available tools. Results: GC1F allele and GC1F/1F genotype were found to confer COPD risk in overall meta-analysis. GC1S/1S was found to confer risk only among Europeans. In silico investigation of rs4588 and rs7041 identified strong eQTL effects and potential role in regulation of GC expression. Large differences in allele frequencies, linkage disequilibrium (LD) and haplotypes were identified at GC locus across different populations (Japanese, African, Europeans and Indians), which may explain the variable association of different GC alleles in different populations. Conclusion: GC1F and GC1F/1F impose significant genetic risk for COPD, among Asians. Considerable differenced in allele frequencies and LD structure in GC locus may impose population specific risk.